The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s40634-021-00356-9
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive scoping review of tibial cysts after anterior cruciate ligament reconstruction

Abstract: Purpose The purpose of this study was to perform a scoping review of published literature reporting on surgical management of tibial cysts which developed after ACLR. Methods A scoping review was conducted following the Arksey and O’Malley framework for scoping studies and Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) extension for scoping reviews (PRISMA-ScR) guidelines. A search strategy using the terms [“Tibial Cyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…This information can be used to guide clinical decision-making in ACLR because many studies have previously shown metal interference screws to provide superior outcomes compared with bioabsorbable screws. This meta-analysis demonstrates that bioabsorbable screws may offer superior outcomes, which is useful information that can be used to guide clinical decision-making, as much of the current literature details the high rates of failure and postop complications of using bioabsorbable screws 39-41 .…”
Section: Discussionmentioning
confidence: 88%
“…This information can be used to guide clinical decision-making in ACLR because many studies have previously shown metal interference screws to provide superior outcomes compared with bioabsorbable screws. This meta-analysis demonstrates that bioabsorbable screws may offer superior outcomes, which is useful information that can be used to guide clinical decision-making, as much of the current literature details the high rates of failure and postop complications of using bioabsorbable screws 39-41 .…”
Section: Discussionmentioning
confidence: 88%
“…Si bien no encontramos casos similares en la literatura, el desarrollo de quistes sinoviales postoperatorios ha sido descrito en otras localizaciones en relación con el uso de tornillos bioabsorbibles, reacción al material de sutura, aumento de la producción de líquido sinovial, necrosis del tendón y micromovimiento. 28 Este estudio presenta ciertas limitaciones debido a su diseño metodológico y el seguimiento relativamente corto de la muestra. Además, a pesar de que nuestra muestra no incluyó pacientes con pie bot sindrómico o neuromuscular, sí evaluó pacientes con características de pie bot idiopático y complejo/atípico.…”
Section: Autoresunclassified
“…Tibial cysts related to the tibial screw are more commonly reported in literature than femoral ones. However, femoral cysts might also occur when the femoral fixation is performed with an interference screw from outside in and those cysts may damage adjacent soft tissue structures [7] .…”
Section: Introductionmentioning
confidence: 99%